Evaluasi Efektivitas Kebijakan Tax Holiday Dalam Meningkatkan Investasi di Indonesia - Chairil Anwar Pohan; Notika Rahmi; Pebriana Arimbhi; Indah Mawarni; Maria Apriliani J. Tembaru (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2021)
This study aims to evaluate the effectiveness of the tax holiday policy in increasing investment in Indonesia, as well as what factors are the obstacles and drivers in the implementation of the tax holiday policy. The research approach used in this research is a descriptive qualitative approach with data collection techniques in triangulation of sources, in-depth interviews, observation, literature study/ documentation. The results of the study found that every year there was a significant increase in terms of foreign investment, but in fact only a few received tax holiday facilities, even in 2017 practically no new registrants were interested in the tax holiday tax incentive. This study concludes that the tax holiday policy is quite effective in increasing investment in Indonesia, but its achievement has not been optimal, and in implementing the tax holiday policy it still faces several obstacles. Among the obstacles in its regulation is the problem of the absence of tax holiday facilities for the shipbuilding industry, even though as an archipelago which covers 2/3 of Indonesia's territory, is a sea and a coastal area, the Indonesian state needs a lot of cargo ships for inter-insular shipping and large oceanic vessels (Feeder vessels and Ocean going vessels) as well as fishing vessels from medium to large and modern sizes. The author suggests that the tax authorities revise the current tax holiday policy by adding a maritime sector (for shipbuilding) in the pioneer industry and making several efforts to overcome obstacles such as simplifying licensing, integrating central and regional policies, improving integration of central and regional policies, expanding the socialization of tax holidays and Licensing Services for Integrated Business Electronically or Online Single Submission (OSS), the supervision and inspection of taxpayers conducting Tax Avoidance or Tax Avoidance must be increased so that state tax revenue can be optimized